Penanganan sialolitiasis - Hatta Hasan S (Journal of Dentomaxillofacial Science, 2009)
The health of layer of oral mucosa and pharynx with mastication and respiration functionin the lower phase depend on the adequate flow of saliva. However, the obstruction ofsalivary gland can cause pain and inconvenience to the patient. A 44 year-old malepatient came with pain on bottom part of his tongue. On palpation and an x-raydiagnosed as sialolitiasis. An incision was made followed by the removal of sialolith andsuturing. This sialolith has a diameter of 1.5 centimetres. Post-surgical control wascarried out check the bleeding and operation condition. The patient was prescribed withanalgesic, antibiotic, and antiinflamation. After several controls, the patient has no morecomplaint.